MERAWAT KERUKUNAN MELALUI PERAN TEOLOGI KRISTEN DALAM MENJAGA TOLERANSI BERAGAMA DI TORAJA - Melisa Ryhced Tandi Lolo; Arsiati Minggu, Welni Ta'bi, Damaris Ukka, Agustinus Hardeka (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2026)
This article aims to analyze the role of Christian theology in building and maintaining religious tolerance in Toraja, a region known for its religious diversity and rich local culture. The main problem studied is how the church and Christian teachings can respond to social dynamics and the challenges of modernization without losing the values of love and peace. The method used in this study is a literature study, by reviewing related theological, anthropological, and sociological sources. The results of the study show that the contextualization of Christian theology based on local values such as mutual cooperation, respect for ancestors, and togetherness, can strengthen the practice of tolerance in a pluralistic society. In addition, the local church has been shown to play a strategic role in education, social services, and interfaith dialogue. This study emphasizes the importance of an open, inclusive, and contextual theological approach as an effective means of maintaining harmony between religious communities in Eastern Indonesia.